(4 1/8 + 6 1/4) - 2 1/2
First find the common denominator of the fractions. In this problem the common denominator is 8.
1/4 = 2/8
1/2 = 4/8
(4 1/8 + 6 2/8) - 2 4/8
10 3/8 - 2 4/8
9 11/8 - 2 4/8 = 7 7/8
I am trying to help my son with his homework but I have no Idea on how to solve the problem. If you can please explain step by step how to solve it. (Simplify (4 1/8 + 6 1/4) - 2 1/2 I am lost when it tells me to rename if possible.
4 answers
Thank you Ms Sue. But how did you get 9 11/8 I'm stuck on that last step
Since we can't take a larger number from a smaller one, we have to borrow from the whole number.
1 = 8/8
10 3/8 = 9 11/8
1 = 8/8
10 3/8 = 9 11/8
I would do it this way:
(4 1/8 + 6 1/4) - 2 1/2
first of all, there is no need for the brackets in this case
secondly, I change all my mixed fractions to workable fractions
= 33/8 + 25/4 - 5/2
LCD is 8
= 33/8 + 50/8 - 20/8
= 63/8 or 7 7/8
mixed numbers are "nice" to look at, but totally useless when it comes to doing any real arithmetic with them, especially when it comes to multiplication or division.
(4 1/8 + 6 1/4) - 2 1/2
first of all, there is no need for the brackets in this case
secondly, I change all my mixed fractions to workable fractions
= 33/8 + 25/4 - 5/2
LCD is 8
= 33/8 + 50/8 - 20/8
= 63/8 or 7 7/8
mixed numbers are "nice" to look at, but totally useless when it comes to doing any real arithmetic with them, especially when it comes to multiplication or division.